Lutas subterrâneas na escola pública: uma análise sobre um coletivo autônomo de jovens. - Vitória Beatriz de Araújo Oliveira Silva (2021)
The present paper is a case study that analyzes a group of young people, recently graduated from a public school on the poor neighborhood of Belo Horizonte (MG). It consisted of investigating the elements present in the social practice of these young people, identifying the principles used in the construction of a pedagogical project aimed at the needs of public students, that is, workers in the teaching-learning process. We assume that the school's pedagogical practice is focused on a formation committed to the values of Transnational Capitalism, taking effect in individualistic, competitive, hierarchical and excluding relationships, antagonistic to the struggles that arise in public school education. Thus, when capturing and understanding the resistance mechanisms developed by this group of students, we seek elements that build a Pedagogy that is related to their realities, using the Sociology of Education as a theoretical reference. We will conduct this qualitative research using the case study methodology.